Growth of nanocrystalline Î±-SiC films on Si(100) and SiO2/Si Substrate using Monomethilsilane Single Source by Hot Mesh-CVD - Astuti, Budi (JOURNAL OF NATURAL SCIENCES AND MATHEMATICS RESEARCH, 2015)
Growth of nanocrystalline Î±-SiC film onÂ  Si(100) substrates was carried out using a home-made hot-mesh chemical vapor deposition (hot-mesh CVD) apparatus. Monomethylsilane (MMS) was used as single source gas while hydrogen (H2) as carrier gas. The growth parameter in this experiment are as follow: H2 flow rate 112 sccm, gas feed ratio (H2/MMS) 172 â 345, total gas pressure during growth 120 â 750 Pa, substrate temperature 500 Â°C, W-mesh wire temperature 1800 Â°C and distance between substrate and W-mesh wire 30 mm. The structural properties of the films were analyzed using scanning electron microscopy (SEM) and x-ray diffraction (XRD). For the composition element of the film was investigated using energy dispersive x-ray spectroscopy (EDX). The surface morphology of the silicon and SiO2/Si wafer was shown similar form i.e. smooth surface without any form of the particle and any defect. Based on the XRD result shows the peak of Î±-SiC(100) was observed around 2Î¸ = 33Â°. Furthermore, according to the EDX characterize, the mass percentage of the carbon and silicon element of the films grown on Si(100) and SiO2/Si(100) are 1,65 and 78.54 for films on carbon and 1.85 and 89.56 for silicon, respectively. We can assume the composition value of the Si is not only from the films is formed but also from the Si substrate.